2016
DOI: 10.1038/ki.2015.280
|View full text |Cite
|
Sign up to set email alerts
|

The lymphotoxin β receptor is a potential therapeutic target in renal inflammation

Abstract: Accumulation of inflammatory cells in different renal compartments is a hallmark of progressive kidney diseases including glomerulonephritis (GN). Lymphotoxin β receptor (LTβR) signaling is crucial for the formation of lymphoid tissue, and inhibition of LTβR signaling has ameliorated several non-renal inflammatory models. Therefore, we tested whether LTβR signaling could also have a role in renal injury. Renal biopsies from patients with GN were found to express both LTα and LTβ ligands, as well as LTβR. The L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 80 publications
1
21
0
Order By: Relevance
“…To the best of our knowledge, this study is the first to demonstrate that both receptors play an instrumental role in kidney disease, whereas previous studies have focused on the effect of LTβR activation. 33 In addition, these data raised the fundamental question: by what mechanism does LIGHT aggravate LPS-induced SA-AKI? We speculated that there were two possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first to demonstrate that both receptors play an instrumental role in kidney disease, whereas previous studies have focused on the effect of LTβR activation. 33 In addition, these data raised the fundamental question: by what mechanism does LIGHT aggravate LPS-induced SA-AKI? We speculated that there were two possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…An Fc fusion protein of LTβR, which can neutralize both LTαβ and LIGHT, can block disease symptoms in many mouse models of rheumatic disease, including collagen-induced and adjuvant arthritis, several models of SLE and the Sjögren-syndrome-like salivary gland inflammation of non-obese diabetic mice 131133,145148 . Additionally, genetic deletion of LIGHT protects mice from lung and skin inflammation and tissue remodelling in models of SSc 144,149 .…”
Section: Increasing Tissue Inflammationmentioning
confidence: 99%
“…This is in line with the previously described constitutive expression of the receptor in parenchymal cells and its promotor region suggesting a house keeping function [ 45 ]. Also earlier studies from our group in patients with various forms of glomerulonephritis, demonstrated that LTβR expression was unaltered in inflamed kidneys [ 15 ].…”
Section: Discussionmentioning
confidence: 96%
“…We performed immunohistochemistry as previously described [ 15 , 32 ]. In brief, sections were dewaxed in xylene, rehydrated in a graded series of ethanol, and incubated in 3% hydrogen peroxide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation